Narrating the nation : representations in history, media and the arts - Berger, Stefan; Eriksonas, Linas; Mycock, Andrew (Making sense of history, 2008)
"A sustained and systematic study of the construction, erosion and reconstruction of national histories across a wide variety of states is highly topical and extremely relevant in the context of the accelerating processes of Europeanization and globalization. However, as demonstrated in this volume, histories have not, of course, only been written by professional historians. Drawing on studies from a number of different European nation states, the contributors to this volume present a systematic exploration, of the representation of the national paradigm. In doing so, they contextualize the European experience in a more global framework by providing comparative perspectives on the national histories in the Far East and North America. As such, they expose the complex variables and diverse actors that lie behind the narration of a nation."--Book jacket.